Team-Based Learning - , admin (مجلة الجزيرة للعلوم الصحية; مجلد 10 عدد 2 (2014), 2014)
Team-Based learning (TBL) is a teaching and learning strategy first implemented in business schools by Larry Michelson, a professor of management at university of Central Missouri(Thompson, Schneider et al. 2007) then applied in other higher education disciplines. Medical schools started to use TBL since 1999 (Thompson, Schneider et al. 2007; Tan, Kandiah et al. 2011; Haidet, Levine et al. 2012). TBL is a teacher-directed method that involves active collaborative learning, which promotes the application of knowledge through small group discussions in a single venue with a limited number of faculties present. (Thompson, Schneider et al. 2007; Parmelee, DeStephen et al. 2009; Tan, Kandiah et al. 2011; Khogali 2013).Currently, medical schools around the world implement TBL in different ways, ranging from a single session in a course to a full course (Thompson, Schneider et al. 2007; Parmelee, Michaelsen et al. 2012; Parmelee and Hudes 2012). TBL is considered a milestone with regard to changes in medical education given its greater integration of knowledge and active learning (Zgheib, Simaan et al. 2010) and its uniqueness that it requires students to work in teams to solve problems (Borges, Kirkham et al. 2012).Since its implementation in medical education, many individuals published their experiences, either to describe the way they do it orther results of their experience. The aim of this review article is to reflect on different experiences in terms of TBL’s process, evidence of success, challenges and opportunities. Another objective is to raise questions for further research that may improve the effectiveness of this strategy.